On growth and fluctuation of k-abelian complexity - Cassaigne J; Karhumaki J; Saarela A (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2022)
An extension of abelian complexity, so called k-abelian complexity, has been considered recently in a number of articles. This paper considers two particular aspects of this extension: First, how much the complexity can increase when moving from a level k to the next one. Second, how much the complexity of a given word can fluctuate. For both questions we give optimal solutions. (C) 2017 Elsevier Ltd. All rights reserved.